Analysis of the Learning Organization in the Presidential Security Forces in the Implementation of VVIP Security Operations - Rudiyanto Dahlan; Rachma Fitriati (International Journal of Science and Society, 2023)
VVIP security challenges are becoming increasingly complex and dynamic in the era of globalization and rapid technological change. This research aims to analyze how the Presidential Security Detail (Paspampres) can adapt to these changes through the application of the concept of a learning organization, specifically the five key disciplines proposed by Senge (1997). Through a qualitative approach, this study collected data through interviews and the study of related literature. The results show that by applying the principles of a learning organization, the Paspampres can improve its effectiveness in carrying out VVIP security duties. This research emphasizes the importance of adaptation and continuous learning in ensuring VVIP security amid constant security challenges. The implications of this research are for the improvement of VVIP security in Indonesia through a more adaptive and learning-oriented approach.